2021
DOI: 10.3390/insects12040317
|View full text |Cite
|
Sign up to set email alerts
|

Diaphorina citri Genome Possesses a Complete Melatonin Biosynthesis Pathway Differentially Expressed under the Influence of the Phytopathogenic Bacterium, Candidatus Liberibacter asiaticus

Abstract: Melatonin is synthesized from the amino acid L-tryptophan via the shikimic acid pathway and ubiquitously distributed in both prokaryotes and eukaryotes. Although most of melatonin biosynthesis genes were characterized in several plants and animal species including the insect model, Drosophila melanogaster, none of these enzymes have been identified from the Asian citrus psyllid, Diaphorina citri. We used comprehensive in silico analysis and gene expression techniques to identify the melatonin biosynthesis-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 88 publications
0
1
0
Order By: Relevance
“…Previously, we proved that citrus plants possess a complex metabolic-based defense system against 'Ca. L. asiaticus' and its insect vector [5,[14][15][16]. This defense system relies on numerous metabolic pathways including, but not limited to, leaf volatile organic compounds (VOCs) [12], amino acids (AA), organic acids (OA), fatty acids (FA) [17], leaf pigments [18], phytohormones [19], polyamines (PAs) [20], melatonin [21], the tricarboxylic acid (TCA)-associated compounds, and non-proteinogenic amino acids (NPAAs) such as γ-aminobutyric acid (GABA) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we proved that citrus plants possess a complex metabolic-based defense system against 'Ca. L. asiaticus' and its insect vector [5,[14][15][16]. This defense system relies on numerous metabolic pathways including, but not limited to, leaf volatile organic compounds (VOCs) [12], amino acids (AA), organic acids (OA), fatty acids (FA) [17], leaf pigments [18], phytohormones [19], polyamines (PAs) [20], melatonin [21], the tricarboxylic acid (TCA)-associated compounds, and non-proteinogenic amino acids (NPAAs) such as γ-aminobutyric acid (GABA) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that citrus plants retain several metabolic-based defense responses against 'Ca. L. asiaticus' and its insect vector [3,[28][29][30]. These metabolic-based defense responses include, but are not limited to, leaf volatiles [31], amino, organic, and fatty acids [32], photosynthetic pigments [33], phytohormones [34,35], polyamines [36][37][38], phytomelatonin [39,40], the tricarboxylic acid-(TCA-) associated compounds, and nonproteinogenic amino acids such as γ-aminobutyric acid (GABA) [36].…”
Section: Introductionmentioning
confidence: 99%